Analisis Hambatan Guru IPS dalam Pembelajaran Jarak Jauh Dampak Pandemi Covid-19 di SMP/MTs Kecamatan Gebog Kabupaten Kudus - Ferdianita, Naila Ferdianita Naila; Mulianingsih, Ferani (Sosiolium: Jurnal Pembelajaran IPS, 2021)
This study aims to determine the barriers of IPS teachers in distance learning (PJJ) in Gebog District, Kudus Regency. The results of the analysis show that the covid-19 pandemic makes learning in Gebog District, Kudus Regency done with distance learning (PJJ). IPS teacher barriers in distance learning (PJJ) include; (1) differences in geographical location, (2) limitations of learning infrastructure, (3) passive learners, (4) learning assessment, (5) large learning quota, (6) teacher professional ability. And efforts in overcoming distance learning barriers (PJJ) include; (1) the policy of each school, (2) assignment of work directly (3) provision of study motivation and school visit, (4) grant of study quota from the government, (5) direct collection of duties, (6) increasing the professional ability of teachers in the use of technology and communication.